Bottom-up analysis of telemonitoring costs - Mihevc, Matic (Zdravstveno varstvo, 2024)
Introduction: Telemonitoring improves clinical outcomes in patients with arterial hypertension (AH) and type2 diabetes (T2D), however, cost structure analyses are lacking. This study seeks to explore the cost structureof telemonitoring for the elderly with AH and T2D in primary care and identify factors influencing costs forpotential future expansions.Methods: Infrastructure, operational, patient participation, and out-of-pocket costs were determined using abottom-up approach. Infrastructure costs were determined by dividing equipment and telemonitoring platformexpenses by the number of participants. Operational and patient participation costs were determined byconsidering patient training time, data measurement/review time, and teleconsultation time. The change inout-of-pocket costs was assessed in both groups using a structured questionnaire and 12-month expendituredata. Statistical analysis employed an unpaired sample t-test, Mann-Whitney U test, and chi-square test.Results: A total of 117 patients aged 71.4±4.7 years were included in the study. The telemonitoring interventionincurred an annual infrastructure costs of €489.4 and operational costs of €97.3 (95% CI 85.7-109.0) per patient.Patient annual participation costs were €215.6 (95% CI 190.9-241.1). Average annual out-of-pocket costs for bothgroups were €345 (95% CI 221-469). After 12 months the telemonitoring group reported significantly lower out-of-pocket costs (€132 vs. €545, p<0.001), driven by reduced spending on food, dietary supplements, medicalequipment, and specialist check-ups compared to the standard care group.Conclusion: To optimise the cost structure of telemonitoring, strategies like shortening the telemonitoringperiod, developing a national telemonitoring platform, using patient devices, integrating artificial intelligenceinto platforms, and involving nurse practitioners as telemedicine centre coordinators should be explored.
Keywords: costs; diabetes; elderly; hipertenzija; hypertension; primarno zdravstveno varstvo; primary care; sladkorna bolezen; starejši; stroški; telemonitoring